2018
DOI: 10.1039/c8ob01881b
|View full text |Cite
|
Sign up to set email alerts
|

Visible light catalyzed reaction of α-bromochalcones with chalcones: direct access to the urundeuvine scaffold

Abstract: The α-keto vinyl radicals generated from α-bromochalcones under visible light photoredox catalyzed conditions were trapped by chalcones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“… A subsequent intermolecular and intramolecular cascade reaction with a heteroarene, such as furans, benzofurans, pyrroles, and indoles generates polycyclic heteroarenes ( 36.3 ) in high yields. The intramolecular reductive cyclization of α-bromochalcones has since been extended in the synthesis of urundeuvine and phenanthrenes derivatives and in the intermolecular coupling of alkenes …”
Section: Inorganic/organometallic Photoredox-catalyzed C–h Functional...mentioning
confidence: 99%
“… A subsequent intermolecular and intramolecular cascade reaction with a heteroarene, such as furans, benzofurans, pyrroles, and indoles generates polycyclic heteroarenes ( 36.3 ) in high yields. The intramolecular reductive cyclization of α-bromochalcones has since been extended in the synthesis of urundeuvine and phenanthrenes derivatives and in the intermolecular coupling of alkenes …”
Section: Inorganic/organometallic Photoredox-catalyzed C–h Functional...mentioning
confidence: 99%
“…In another article, Paria and coworkers [195] revealed a photoredox iridium complex catalyzed intermolecular couplings of α‐bromochalcones to olefins affording 3,4‐dihydronaphthalenes (reaction 5, Figure 49) that can be easily transformed to the corresponding naphthalenes and further cyclized to 5 H ‐benzo[c]fluorenes. Another groupof researchers [196] investigated the visible light catalyzed reaction of α‐Br‐chalcones with α‐unsubstituted chalcones that led to the synthesis of dihydronaphthalenes, which were oxidized to the corresponding naphthalenes (reaction 6, Figure 49). This strategy was employed to prepare derivatives of the natural urundeuvine chalcones.…”
Section: Different α‐Substituted Chalconesmentioning
confidence: 99%
“…In a variation of these processes, Rastogi and co-workers subsequently showed that chalcones 19 can also be utilized in such sequences instead of simple alkenes to give rise to dihydronaphthalenes 20 , which could be further dehydrogenated to the corresponding naphthalenes 21 (Scheme ). Moreover, rather than by trapping with an external heteroarene, cyclization into an arene placed at an appropriate position of the α-bromochalcone can also be achieved. In this way, the intramolecular cyclization of vinyl radicals 23 was possible, enabling the synthesis of substituted phenanthrenes 25 …”
Section: Activation Of Vinyl Halides By Visible-light Photocatalysismentioning
confidence: 99%